Dynamics of Electron Flux in the Slot Region and Geomagnetic Activity - L. Nikitina; L. Trichtchenko (Space Weather)
Abstract The slot region between the radiation belts in the magnetosphere is statistically less populated by the energetic electrons, which makes it attractive in the design considerations of the satellite missions. As has been shown in the last decades, the dynamics of this region is complicated, with strong enhancements of electron density associated with space weather events. This paper provides an analysis of the dynamics of electron flux in 1998–2007 with specific attention to slot filling events and preceding geomagnetic activity. Flux of energetic electrons, with energies E > 0.63 MeV, E > 1.5 MeV, and E > 3 MeV, was obtained from detectors on board the HEO‐3 satellite in highly elliptical orbit. To evaluate geomagnetic conditions, associated with enhancement of electron flux, all the “slot filling events” were studied together with geomagnetic activity provided by Dst and Kp global indices as well as with the hourly range indices of geomagnetic variations at mid‐latitude. These geomagnetic indices were used for assessment of a threshold and frequency of occurrence of slot filling events. Regression analysis has been used to find a relationship between the maximum filling of the slot region due to space weather event and the preceding geomagnetic activity level. Influence of the cumulative time of periods of enhanced geomagnetic activity to the variation of the electron flux in the slot region has been analyzed. Suitability of different indices of geomagnetic activity for estimation of the rate of occurrence of slot filling events and for assessment of electron flux in the slot region is discussed.